(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
Magnoliaceae is a family of dicotyledonous plants. Consists of trees and shrubs.The leaves are entire, sometimes lobed, the margins are flat, the flowers are large, straight, bisexual (rarely homogeneous). There are many pollinators. There are 14 genera (about 240 species) in the tropical and subtropical regions of America and Asia. Magnolia and tulip species are cultivated as ornamental plants.